Self-care for academics: a poetic invitation to reflect and resist. Issue 2 (4th March 2018) - O'Dwyer, Siobhan; Pinto, Sarah; McDonough, Sharon
Abstract: In newspapers and blogs, on Twitter, and in academic papers, stories of struggling academics abound. Substance abuse, depression, failed relationships, and chronic illness are the casualties of a neoliberal university sector that values quantity over quality and demands ever more for ever less. Within the academic literature a growing counter-movement has called for resistance, collective action, and slow scholarship. Much of this work, however, has focused on strategies that can be applied within academia. Little has been written about the activities that academics do outside the university; activities that have no purpose other than enjoyment, rest, and renewal; activities that represent the valuing of the self as a human being, rather than a means of production; activities that could best be defined as self-care. Using reflective practice to construct a poem comprising three voices, this paper explores those activities. This poetic representation is an effort to create time and space for the authors, and a manifesto to encourage other academics to demand and protect the time, space, and reflective practice that are essential to both personal wellbeing and quality research and education.